Revaccination of Guinea Pigs With the Live Attenuated Mycobacterium tuberculosis Vaccine MTBVAC Improves BCG's Protection Against Tuberculosis. (25th January 2017) - Clark, Simon; Lanni, Faye; Marinova, Dessislava; Rayner, Emma; Martin, Carlos; Williams, Ann
Abstract: Background: The need for an effective vaccine against human tuberculosis has driven the development of different candidates and vaccination strategies. Novel live attenuated vaccines are being developed that promise greater safety and efficacy than BCG against tuberculosis. We combined BCG with the vaccine MTBVAC to evaluate whether the efficacy of either vaccine would be affected upon revaccination. Methods: In a well-established guinea pig model of aerosol infection with Mycobacterium tuberculosis, BCG and MTBVAC delivered via various prime-boost combinations or alone were compared. Efficacy was determined by a reduction in bacterial load 4 weeks after challenge. Results: Efficacy data suggests MTBVAC-associated immunity is longer lasting than that of BCG when given as a single dose. Long and short intervals between BCG prime and MTBVAC boost resulted in improved efficacy in lungs, compared with BCG given alone. A shorter interval between MTBVAC prime and BCG boost resulted in improved efficacy in lungs, compared with BCG given alone. A longer interval resulted in protection equivalent to that of BCG given alone. Conclusions: These data indicate that, rather than boosting the waning efficacy of BCG, a vaccination schedule involving a combination of the 2 vaccines yielded stronger immunity to M. tuberculosis infection. This work supports development of MTBVAC use as a revaccination strategy to improve on the effects of BCG in vaccinated people living in tuberculosis-endemic countries.